Exploring the relationship between smoking and poor sleep quality: a cross-sectional study using NHANES - Sun, Haoxiong; Li, Sijia (Frontiers in Psychiatry, 2024)
Introduction: Sleeping disorders is a high prevalent disorder, and although previous research has suggested a link between smoking and sleep disorders, there is a lack of large-scale, nationally representative studies examining this association across multiple sleep outcomes and exploring dose-response relationships. Methods: This study used data from 30,269 participants from the NHANES database (2007-2020). Weighted logistic regression models were used to assess the associations between smoking status (non-smoker, light smoker, moderate smoker, and heavy smoker) and various sleep outcomes, including insufficient sleep duration, reported sleep problems, snoring, snorting, or stopping breathing during sleep, and daytime sleepiness. Dose-response relationships were explored using restricted cubic splines. Results: Compared to non-smokers, heavy smokers had significantly higher odds of experiencing insufficient sleep duration with OR 1.732 (95% CI 1.528-1.963, P <0.001), reported sleep problems with OR 1.990 (95% CI 1.766-2.243, P <0.001), occasional or frequent snoring with OR 1.908 (95% CI 1.164-3.128, P = 0.03), and occasional or frequent snorting or stopping breathing during sleep with OR 1.863 (95% CI 1.183-2.936, P = 0.022), while results for sometimes, often or almost always being overly sleepy during the day with OR 1.257 (95% CI 0.872-1.810, P = 0.115) are not significant. A trend of positive correlation was observed between smoking and all sleep disorder outcomes (P for trend < 0.05). Dose-response analyses revealed that the odds of these sleep outcomes increased with higher smoking levels. Conclusion: Smoking is significantly associated with various sleep disorders, and a dose-response relationship exists between smoking levels and the odds of experiencing these sleep problems. These findings underscore the importance of addressing smoking as a modifiable risk factor for poor sleep health and suggest that reducing smoking, even if complete cessation is not achieved, may have positive effects on sleep outcomes.